Pedagogical case of marketing strategies during the Covid-19 pandemic: The extraordinary case of Chanel - Pereira, Ana Margarida Marcelino Oliveira (2022)
Due to Covid-19, many businesses and industries suffered with the pandemic. Luxury was one of those areas: products belonging to this commercial segment went through transformations about their distribution channels, with the purpose of maintaining sales or at least allowing the business to continue. This pedagogic case focuses on this thematic: analyzing how luxury brands were able to survive in a period of commercial uncertainty. Particularly, it studies Chanel and its response to the online paradigm during the Covid-19 pandemic. This master thesis addresses the company’s history, its business model, the digital transformation’s impact on luxury and what was verifiable, succinctly, in terms of marketing strategies during the pandemic, for diverse luxury brands (concentrating on Chanel). The target for this thesis is either students of Marketing and/or Luxury, investigators of these areas or luxury enthusiasts. With this pedagogic case, it is expected that the target can develop their insights from the pandemic era whilst also managing to creatively respond to the case study questions. The ultimate and master goal for this thesis is to broaden the horizons of the industry, specifically Chanel, on all the new possibilities in this digital new paradigm. With an extensive literary and factual search, the results showed that the marketing strategies chosen by Chanel not only have a distinct weight on the conservation of values such as exclusivity, but also a positive aspect for the financial recovery of the brand after the pandemic.